Innovations in invasive parasite control: enhancing nest treatment techniques to combat the threat of the avian vampire fly Philornis downsi in Galapagos - Kofler, Barbara; Mauchamp-Fessl, Merlin; Poveda-Pazmiño, Cristian; Causton, Charlotte E.; Tebbich, Sabine; Fessl, Birgit (Frontiers in Conservation Science, 2025)
The invasive parasitic nest fly Philornis downsi poses a severe threat to the conservation of Galapagos’ endemic landbirds, including Darwin’s finches. Therefore, the development of effective stop-gap methods is required to mitigate its harmful impact until long-term solutions are found. This study aims to enhance the usability of two insecticide-based control methods designed to reduce fly infestation: 1) Self-fumigation during which birds incorporate insecticide-treated nesting material into their nests, and 2) the Spritz technique, which involves spraying insecticide around the nest entrance to prevent female flies from entering nests to lay eggs. To improve the efficacy and broaden the applicability of self-fumigation across species, we tested the effects of two insecticides using this method (Cyromazine and Permacap CS®) on per-nest P. downsi abundance and fledging success in three Darwin’s finch species, Small Ground-finch (Geospiza fuliginosa), Small Tree-finch (Camarhynchus parvulus), and Green Warbler-finch (Certhidea olivacea). We employed a stepwise approach to optimize method efficacy through variation in the insecticide used and its dosage, dispenser setup, and the type of material offered to birds. Cyromazine was effective in reducing P. downsi abundance, but did not result in increased fledging success. Permacap-treated materials at 0.5% and 1% concentrations significantly increased fledging success. Four nesting materials offered in dispensers placed 4 m high were widely accepted by Darwin’s finches. For the Spritz technique, we also tested the effects of the two Permacap concentrations on P. downsi abundance and fledging success over two consecutive breeding seasons. Using a novel, lightweight, and pole-compatible spraying device with 0.5% Permacap, fledging success improved significantly across all tested finch species, while minimizing nest abandonment risk. These methods offer immediate, effective solutions for P. downsi control, and for improving fledging success in Darwin’s finches, potentially reducing extinction risks for some of the Galapagos’ most threatened species, and marking a critical step in preserving the archipelago’s unique avian diversity.